(Un)silencing the Silence: EFL Students’ Speaking Anxiety in Answering Lecturers’ Questions - Mukhlash Abrar; Muhammad Muldan Salim; Rd. M. Ali; Felipa M. Rico (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2024)
This study attempts to explore the factors and strategies of EFL students' speaking anxiety in answering the lecturer's questions. A qualitative design using a case study method was employed to gather information about individual experiences. This study examined EFL students' speaking anxiety when responding lecturers' questions at a Jambi public university. The researchers selected 10 active EFL students who had finished all courses, were accessible, and eager to engage in this research. The researchers collected data through interviews and supervisor notes. The findings were analyzed thematically. Linguistics and knowledge issues (grammar, vocabulary, pronunciation, and lack of knowledge), psychological issues (fear of making mistakes, lack of confidence, and lack of motivation), and performance issues (lack of preparations, environmental conditions, and time pressure) were identified. This study also found that EFL students reduce anxiety through self-management (practice and preparation, learning from mistakes), self-psychology (relaxation and motivation), and help from others (friends and family).